Prosedur Pendaftaran Merek Usaha Mikro Di Dinas Koperasi Dan Usaha Mikro Kabupaten Malang - Ilmi Nafiatul Amala; Wahyu Retno Sari; Mochamad Ali Septia Rozikin; Indra Luqmana; Yenie Eva Damayanti (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in driving the Indonesian economy. However, many MSMEs do not understand the importance of business legality and trademark registration. This can hinder their business development and access to capital. To overcome this problem, the Cooperatives and Micro Enterprises Office of Malang Regency conducted socialization and consultation on trademark registration procedures for MSMEs. Socialization is carried out face-to-face using PowerPoint presentations to explain the process of trademark registration and the benefits of owning a brand. Followed by individual consultations to help MSMEs. The success of the activity is measured through questionnaires before and after the activity to assess the understanding of MSMEs. The trademark registration process for MSMEs includes verification of availability, submission of applications to the Directorate General of Intellectual Property, completion of requirements, and waiting for announcement. Brands are very important for MSMEs because they facilitate product identification, protect product characteristics, create a company image, and attract loyal customers. Therefore, socialization regarding business legality and brand interests needs to continue to be carried out to help the growth of MSME businesses.